The Impact of Islamic Economic Law on Financial Regulation: Evidence from the Indonesian Dual Financial System: Dampak Implementasi Hukum Ekonomi Islam terhadap Regulasi Keuangan: Kajian Sistem Keuangan Ganda Indonesia - Maulana Ihsan Yusufi Suyatno; Anisa Kusumawardani; Mirna Dyah Praptitorini; Primadhani Dyah Larasati Suyatno (Al Dzahab, 2025)
Purpose: This study examines the impact of Islamic Economic Law on financial regulation within the context of Indonesia’s dual financial system, while addressing the research gap that rarely explores regulatory challenges arising from the integration of conventional and Islamic frameworks. Design/Methodology/Approach: Employing a mixed-methods approach, this research combines qualitative data from 15 stakeholders—including regulators, academics, and practitioners—with secondary data drawn from institutional reports and reputable journals (2018–2024). Findings: The results reveal that Islamic Economic Law enhances regulatory ethics and transparency. The integration of Islamic finance fosters financial inclusion. Although the dual financial system offers potential synergies, its implementation remains hindered by regulatory fragmentation and low public literacy. Research Implications: This study contributes both theoretically—by linking Maqasid al-Shariah to an inclusive regulatory framework—and practically, by providing recommendations for regulatory harmonization between OJK and DSN-MUI, improving financial literacy, and fostering product innovation. The findings affirm Indonesia’s position as a potential global reference for the integration of ethical finance.